The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1097/sap.0000000000002373
|View full text |Cite
|
Sign up to set email alerts
|

Free Medial Plantar Flap Versus Free Dorsal Myocutaneous Flap for the Reconstruction of Traumatic Foot Sole Defects

Abstract: Background Trauma can cause large defects in the weight-bearing foot sole. The reconstruction of such defects poses a major challenge in providing a flap that is durable, sensate, and stable. The pedicled medial plantar flap has been commonly used for reconstructing heel and plantar forefoot defects; however, the ipsilateral instep region is usually compromised by trauma. The purpose of this article was to report the use of contralateral free medial plantar flaps for the coverage of weight-bearing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
34
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(34 citation statements)
references
References 27 publications
0
34
0
Order By: Relevance
“…Our results do not match with the findings of other authors . [ 20 , [29] , [30] , [31] , [32] ] Analyzing our results and comparison between both flaps, we found that lateral supramalleolar artery flap provides excellent coverage to the dorsum of the foot up to the metatarsophalangeal joint. The advantages of the flap are easy dissection, robust pliable skin, flexibility in rotation of flap, and allow excellent coverage of dorsal skin defects of ankle and feet up to toes contrary to the belief that it cannot cover the dorsum of foot [ 31 ].…”
Section: Discussionmentioning
confidence: 94%
See 2 more Smart Citations
“…Our results do not match with the findings of other authors . [ 20 , [29] , [30] , [31] , [32] ] Analyzing our results and comparison between both flaps, we found that lateral supramalleolar artery flap provides excellent coverage to the dorsum of the foot up to the metatarsophalangeal joint. The advantages of the flap are easy dissection, robust pliable skin, flexibility in rotation of flap, and allow excellent coverage of dorsal skin defects of ankle and feet up to toes contrary to the belief that it cannot cover the dorsum of foot [ 31 ].…”
Section: Discussionmentioning
confidence: 94%
“…This is a big difference between the previous studies and mine. There is tremendous literature support in favor of sural artery flap for coverage of lower leg, foot, ankle, and perimalleolar areas [ 20 , 23 , [29] , [30] , [31] , [32] ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Superficial, non‐infected ulcers can be treated conservatively very well (Malhotra et al, 2012). Persistent or infected wounds require a multidisciplinary approach for wound care, incorporating serial debridement followed by definitive soft‐tissue reconstruction (Chou et al, 2018; Crowe et al, 2019; Deiler et al, 2000; Elgohary et al, 2018; Fox et al, 2015; Han et al, 2020; Khai Luen & Wan Sulaiman, 2017; Kim et al, 2016; Kimura et al, 2003; Koshima et al, 2001; Nahai et al, 1978; Park et al, 2017; Rainer et al, 2003; Santanelli et al, 2002; Song et al, 2016; Van Landuyt et al, 2005; Yamamoto, 2019; Yamamoto et al, 2016, 2019, 2020). In the current literature, further or exemplary soft‐tissue involvement is not addressed in the treatment regimens.…”
Section: Discussionmentioning
confidence: 99%
“…There are several articles reporting free flap reconstructions for heel soft tissue defects (Table 1) (Al Maksoud et al, 2016; Chou et al, 2018; Elgohary et al, 2018; El‐Shazly et al, 2008; Grauberger et al, 2020; Han et al, 2020; Kang et al, 2013; Khai Luen & Wan Sulaiman, 2017; Kim et al, 2016; Kuran et al, 2000; Liu et al, 2014; Oh et al, 2011; Park et al, 2017; Song et al, 2016; Van Landuyt et al, 2005; Yücel et al, 2000). Medial plantar and medialis pedis (MP) flap are ones of the most popular flaps for heel reconstruction, mainly as pedicled flaps.…”
Section: Discussionmentioning
confidence: 99%